Професійний розвиток персоналу згідно умов трансформацій у підприємництві - Драган, Олена Іванівна; Бергер, Аліна Дмитрівна; Мізюк, Анна Олексіївна (My University, 2024)
У статті досліджується професійний розвиток персоналу в умовах непередбачуваних змін і постійних трансформацій у системі підприємництва. Водночас трансформації в підприємництві свідчать про переформатування на нові бізнес-підходи у сфері торгівлі, надання індивідуальних послуг, виробництво продукції для воєнних цілей, ІТ тощо. Тому, провідні компанії-роботодавці усвідомлюють важливість підтримання професійного розвитку співробітників, а саме: удосконалення своїх Soft і Hard Skills, здійснення перекваліфікації згідно вимог діджиталізації бізнесу. Проаналізовано сутність категорії «професійний розвиток персоналу» згідно підходів: системний, процесний і мотиваційний. Дискусійним є авторське визначення поняття «професійний розвиток персоналу» як мотиваційної складової успішності та реалізації сучасного працівника у професійній діяльності. Обґрунтовано, що особистісний розвиток і соціальний розвиток сприяють формуванню Soft Skills працівників, а професійний розвиток ‒ Hard Skills. Опитування топ-менеджменту вітчизняних компаній стосовно визначення пріоритетних Soft Skills свідчить про вагомість стресостійкості, лідерських якостей і критичного мислення. Водночас стосовно Hard Skills на перше місце керівники ставлять: стратегічне мислення, персональну відповідальність та бізнес-аналітику (економічний результат). При обранні способу навчання топ-менеджмент надає перевагу онлайн навчанню і сертифікованим програмам фахової спрямованості з високою репутацією.

Professional development of personnel in the conditions of unpredictable changes, permanent transformations in the system of the enterprise is investigated in the article. Considerably became complicated from full-scale war and negative unpredictable changes of functioning system of the enterprise in Ukraine: absence of personal safety; migration of highly skilled talented workers; risks of property loss are the result of destruction; cardinal changes in legislation; external economic limitations; increase of the amount of people who are not able to execute the obligations in the enterprises; companies closing and business relocation abroad. At the same time, transformations in the enterprise testify to the reformatting on new business-approaches in the field of trade, grant of individual services, production of goods for soldiery aims, IT and others like that. Thus, regardless to the terms of war, leading companies-employers realize importance of maintenance of professional development of employees. In particular, force of feed-back, when the best professionals value work in the company, that helps them to grow professionally. In addition, professional development is important for workers on a few reasons, such as: helps to improve Soft and Hard Skills, to carry out retraining, be in a course the last tendencies in a business-sector. Scientific achievements in relation to maintenance of essence of category “professional development of personnel” in obedience to approaches: system, process and motivational are analyzed and generalized. Debatable is authorial determination of concept “professional development of personnel” as motivational component of success and realization of worker. Reasonably, that personality development and social development assist forming of workers’ Soft Skills. And the professional development of workers, aimed at forming of Hard Skills. Questioning of top-management of domestic companies in relation to the determination of priority Soft Skills testifies to ponderability of stress resistance, leader qualities and critical thinking. Questioning of top-management of domestic companies testifies that into first place leaders put next Hard ‒ the strategic thinking, personal responsibility and analytic business-geometry. During the electing method of studies a top-management gives advantage to on-line education and certificated programs of professional orientation with high reputation.
Keywords: кафедра економіки праці та менеджменту; кафедра маркетингу; підприємництво; професійний розвиток; персонал; система; трансформації; способи навчання; опитування; entrepreneurship; professional development; personnel; system; transformations; Soft Skills; Hard Skills; learning methods; surveys